A B(12)-dependent radical SAM enzyme involved in Oxetanocin-A biosynthesis - Bridwell-Rabb, Jennifer (Nature, 2017)
Oxetanocin-A (OXT-A, 1) is a potent antitumor, antiviral, and antibacterial compound. Biosynthesis of OXT-A has been linked to a plasmid-borne, Bacillus megaterium gene cluster that contains four genes, oxsA, oxsB, oxrA, and oxrB. Here, we show that the oxsA and oxsB genes are both required for the production of OXT-A. Biochemical analysis of the encoded proteins, a cobalamin (Cbl)-dependent S-adenosylmethionine (AdoMet) radical enzyme, OxsB, and an HD-domain phosphohydrolase, OxsA, revealed that OXT-A is derived from 2′-deoxyadenosine phosphate in an OxsB-catalyzed ring contraction reaction initiated by H-atom abstraction from C2′. Hence, OxsB represents the first biochemically characterized non-methylating Cbl-dependent AdoMet radical enzyme. X-ray analysis of OxsB reveals the fold of a Cbl-dependent AdoMet radical enzyme for which there are an estimated 7000 members. Overall, this work provides a framework for understanding the interplay of AdoMet and Cbl cofactors and expands the catalytic repertoire of Cbl-dependent AdoMet radical enzymes.